Reading, Finding, Discussing, and Talking Learning Model with Socio-Scientific Issues and Islamic Values for Scientific Literacy - Zuhair Abdullah; Dian Rif’iyati; Andhin Oktovania Ramadhani (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a Reading, Finding, Discussing, and Talking (RFDT) learning model that encompasses socio-scientific issues and Islamic values to improve students' scientific literacy. This model is considered more comprehensive in developing students' knowledge and skills. The research method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The sample in the study amounted to 48 students taken using a simple random sampling technique. Data were collected through observation techniques, interviews, validation questionnaires, and scientific literacy tests, then descriptive analysis was carried out using normalized gain and inferential analysis using an independent t-test. The results showed that the developed model was considered very valid by experts with an average score of 4.43. The application of the model showed an increase in acquisition scores in the experimental class compared to the control class, although the t-test results did not show a significant difference (p > 0.05). Several possible causes for the insignificant t-test results include the small number of samples and teachers still in the adaptation stage to the model. However, this model received a positive response from students so it is suitable for use in integrative, contextual, and religious learning.